Solar pond conception - experimental and theoretical studies - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
A one dimensional transient mathematical model for predicting the thermal performance of the salt gradient solar pond is developed and presented. In this paper, the natural solar ponds and different artificial solar pond systems found in the literature are introduced. Necessary modifications are made on the experimental stand located in Istanbul Technical University, the experimental stand is introduced and natural phenomena produced in the pond by the different solar pond variations under natural conditions are observed. In the theoretical work based on a one dimensional unsteady state heat conduction model with internal heat generation, the energy and mass balance equations for the upper convective zone, the non-convective zone and the lower convective zone, all of which form the solar pond, are written in terms of differential equations. These equations are solved analytically and numerically. The results obtained from the analysis are compared with the experimental results. The temperature and the concentration profiles are separately presented in the figures. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: solar pond; mathematical model; experimental study; SIMULATION